Implementasi Dashboard Multi-Role pada Sistem Afiliasi dan Marketplace Berbasis Web PT. BIZHUB DIGITAL INDONESIA - Bayu Setiawan; Rajawali Shaktika Anugrah Prasetya; Andra Husnul Azmi; Hazna At Thooriqoh (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Digital marketing encourages companies to adopt systems capable of managing transactions, affiliate partners, commissions, and performance reports within a single integrated platform. Previously, PT Bizhub Digital Indonesia relied on third-party platforms to operate its affiliate marketing activities. This condition limited the company's flexibility in managing workflows, monitoring affiliate performance, and independently handling commission disbursements. This study aims to implement a multi-role dashboard within a web-based affiliate and marketplace system. The system was designed to accommodate three primary user roles: Admin, Member/Affiliator, and Customer. The research methodology consisted of requirements analysis, system design using use case diagrams, activity diagrams, and sequence diagrams, web-based interface implementation, and functional testing through the black-box testing method. The implementation results demonstrate that the multi-role dashboard effectively separates system functionalities according to user access privileges. Administrators are able to manage products, categories, transactions, affiliate data, ratings, and commission withdrawals. Members/Affiliators can generate affiliate links, monitor referral transactions, track commission balances, and submit withdrawal requests. Customers can browse product catalogs, complete purchases, view order histories, manage profiles, and provide product ratings. The testing results indicate that all major system features functioned according to the predefined test scenarios. Therefore, the implemented multi-role dashboard supports the management of affiliate and marketplace systems in a more structured, transparent, and operationally efficient manner, while meeting the specific business requirements of the company.